ANALISIS PEMBIAYAAN BTPN SYARIAH TERHADAP PENINGKATAN EKONOMI MASYARAKAT DI TANGGAMUS - Raden Ayu Salsabila; Noorikha Pandayahesti Saputeri; Warsiyah (Program Studi Ekonomi Syariah, 2026)
This study aims to analyze the impact of BTPN Syariah financing on improving the local economy in Tanggamus Regency. The main issue examined is how Islamic financing contributes to local economic growth and community welfare. This research employs a qualitative method with data collection techniques including field observations, in-depth interviews, and documentation as supporting methods to complement the necessary data. The findings reveal that BTPN Syariah financing has a positive impact on the community's economy in Tanggamus. Several factors influence the effectiveness of the financing, including: a personal and non-bureaucratic approach that fosters comfort and trust among the community; a simple process with minimal requirements and fast processing time, which aligns well with the characteristics of rural communities; a comprehensive mentoring program that ensures the sustainability of customers' businesses; and the use of various types of Sharia contracts that provide flexibility according to customers' needs